Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.10
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Scatter TSP in Doubling Metrics

Abstract: We study the problem of finding a tour of n points in which every edge is long. More precisely, we wish to find a tour that visits every point exactly once, maximizing the length of the shortest edge in the tour. The problem is known as Maximum Scatter TSP, and was introduced by Arkin et al. (SODA 1997), motivated by applications in manufacturing and medical imaging. Arkin et al. gave a 0.5-approximation for the metric version of the problem and showed that this is the best possible ratio achievable in polyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…(Such instances of MV-TSP arise e.g. in the Maximum Scatter TSP application by Kozma and Mömke [37]. )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Such instances of MV-TSP arise e.g. in the Maximum Scatter TSP application by Kozma and Mömke [37]. )…”
Section: Discussionmentioning
confidence: 99%
“…(For instance, we may snap input points to nearby grid points, if doing so does not significantly affect the objective cost.) Recently, this technique was used by Kozma and Mömke, to give an efficient polynomial-time approximation scheme (EPTAS) for the Maximum Scatter TSP in doubling metrics [37], addressing an open question of Arkin et al [4]. In this case, the reduced problem is exactly the MV-TSP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kozma and Mömke [36] showed that there is a PTAS for the MSTSP in doubling spaces of dimension d at most O(log log n), where n is the number of vertices. More precisely, the result is a (1 + ε)-approximation algorithm running in timeÕ 1) .…”
Section: Doubling Spacesmentioning
confidence: 99%
“…(For instance, we may snap input points to nearby grid points, if doing so does not significantly affect the objective cost.) Recently, this technique was used by Kozma and Mömke, to give an efficient polynomialtime approximation scheme (EPTAS) for the Maximum Scatter TSP in doubling metrics [29], addressing an open question of Arkin et al [4]. In this case, the reduced problem is exactly the MV-TSP.…”
Section: Introductionmentioning
confidence: 99%